TECHNOLOGY OF PREPARATION OF DIDACTIC GAME TASKS IN TEACHING THE SCIENCE OF MEDICAL TECHNOLOGY AND MEDICAL TECHNOLOGIES IN HIGHER MEDICAL EDUCATIONAL INSTITUTIONS - Bozorov Erkin Khozhyevich.; Nabiev Abdullo Abduvakhidovich (Western European Studies, 2025)
In the article, when choosing didactic games in teaching medical technology and medical technology, the prospects for the near future development of medical technology, the choice of performance indicators based on further technical improvement of devices and the widespread use of elements. didactic games in them, the experience of communicating with peers and adults are considered. It is thought that this will help comprehensive development and awaken interest in educational activities
Keywords: Medical Equipment And Medical Technologies; Didactic Games; Educational Activity